Capacity Efficiency Improvment And Innovation Technology Transfer Of Dairy Cow Feed Processing At Dairy Cow Farm Center, Brau Village, Batu City - Evi Kurniati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
Batu City has a potential livestock (rabbits, beef cattle, and dairy cows). Brau Village in Batu City is one of the centers of dairy cow farmers and they are the member of business cooperative